2010
DOI: 10.1017/s1751731110000297
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with selling price of cattle at livestock marts

Abstract: The objective of this study was to determine the factors associated with selling price of animals at livestock marts around Ireland. Data consisted of four distinct maturity categories: calves (2 to 84 days of age, n 5 53 838); weanlings (6 to 12 months of age, n 5 19 972); post-weanlings (12 to 36 months of age, n 5 93 081) and cows (.30 months to 12 years of age, n 5 94 839); sold through livestock marts between 2000 and 2008. Factors associated with animal price were determined within each maturity category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 27 publications
3
47
2
1
Order By: Relevance
“…Animal market price A total of 4 207 051 animal market price records (overall animal price rather than price per kg) from 3 552 089 animals sold at 74 livestock auctions in Ireland between the years The data were divided into three distinct maturity categories as described in detail by McHugh et al (2010): calves, weanlings and post-weanlings. The edits implemented were those described by McHugh et al (2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal market price A total of 4 207 051 animal market price records (overall animal price rather than price per kg) from 3 552 089 animals sold at 74 livestock auctions in Ireland between the years The data were divided into three distinct maturity categories as described in detail by McHugh et al (2010): calves, weanlings and post-weanlings. The edits implemented were those described by McHugh et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…The edits implemented were those described by McHugh et al (2010). Calves were defined as animals born from dairy cows (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the value of carcasses from culled cows has been seldom taken into account. McHugh et al (2010) investigated several factors associated with the price of cows sold at livestock marts in Ireland, but did not provide any information on the live animals characteristics, dressing percentage (DP) and slaughter performance. Bazzoli et al (2014) studied the effects of breed and age on the CW and value of slaughtered cows, but did not consider any live animal traits.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, studies reported that higher valuations are reached using particular genetic groups (Halfman et al, 2009;McHugh et al, 2010;Koetz Junior et al, 2014). However, Barham and Troxel (2007) reported that no specific breed or breed type was marketed for higher prices and the superiority of a given group is dependent on the region where the sale occurred and the future prices for the coming years.…”
Section: Resultsmentioning
confidence: 69%